2016
DOI: 10.1088/1361-648x/aa4e0e
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigations into the thermodynamics of cation disorder and its impact on electronic structure and magnetic properties of spinel Co(Cr1–xMnx)2O4

Abstract: Cation disorder over different crystallographic sites in spinel oxides is known to affect their properties. Recent experiments on Mn doped multiferroic CoCr2O4 indicate that a possible distribution of Mn atoms among tetrahedrally and octahedrally coordinated sites in the spinel lattice give rise to different variations in the structural parameters and saturation magnetisations in different concentration regimes of Mn atoms substituting the Cr. A composition dependent magnetic compensation behaviour points to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…, we have demonstrated that the dominant defects in the chalcogenide spinels are anti-sites, signifying that p-type Mg In and n-type In • Mg are the primary intrinsic defects in MgIn 2 S 4 , while Sc • Mg or Mg Sc are the main defects in MgSc 2 S 4 (Se 4 ).These findings are similar to previous computational[75][76][77][78] and experimental 72 studies on ternary oxide spinels, with anti-sites dominating over other intrinsic defects, i.e. vacancies and interstitials.…”
supporting
confidence: 90%
“…, we have demonstrated that the dominant defects in the chalcogenide spinels are anti-sites, signifying that p-type Mg In and n-type In • Mg are the primary intrinsic defects in MgIn 2 S 4 , while Sc • Mg or Mg Sc are the main defects in MgSc 2 S 4 (Se 4 ).These findings are similar to previous computational[75][76][77][78] and experimental 72 studies on ternary oxide spinels, with anti-sites dominating over other intrinsic defects, i.e. vacancies and interstitials.…”
supporting
confidence: 90%
“…The details of calculations of the thermodynamic free energy, and the procedure of estimating the equilibrium y = 0 for a given temperature T and Fe concentration x have also been discussed in ref. . As done in ref.…”
Section: Details Of Calculationsmentioning
confidence: 99%
“…We have modeled the Co(normalCr1xnormalFex)2normalO4 system for various values of x and various degrees of cation disorder y according to the scheme presented in ref. . The details of calculations of the thermodynamic free energy, and the procedure of estimating the equilibrium y = 0 for a given temperature T and Fe concentration x have also been discussed in ref.…”
Section: Details Of Calculationsmentioning
confidence: 99%
See 2 more Smart Citations